2014
DOI: 10.1111/cen.12578
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyrotropin is independently related to Small for Gestational Age neonates at term

Abstract: Our data show that TSH levels in the upper range of the reference interval at different trimesters (3·0-3·29 mIU/l) are independently related to an increased risk of delivering SGA neonates at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…For example, Medici et al indicated no associations between early pregnancy maternal TPO‐Ab positivity and low birthweight. Ong et al in Australia suggested that TPO‐Ab positivity does not increase the risk of SGA, which is consistent with another study conducted by Monen et al However, the results from the Northern Finland Birth Cohort (NFBC) showed that TPO‐Ab‐positive mothers are more susceptible to having both low‐birthweight and LGA infants than are TPO‐Ab‐negative mothers. TPO‐Ab positivity might be a risk factor for birth outcomes, but TPO antibodies themselves could also have an independent effect .…”
Section: Discussionsupporting
confidence: 73%
“…For example, Medici et al indicated no associations between early pregnancy maternal TPO‐Ab positivity and low birthweight. Ong et al in Australia suggested that TPO‐Ab positivity does not increase the risk of SGA, which is consistent with another study conducted by Monen et al However, the results from the Northern Finland Birth Cohort (NFBC) showed that TPO‐Ab‐positive mothers are more susceptible to having both low‐birthweight and LGA infants than are TPO‐Ab‐negative mothers. TPO‐Ab positivity might be a risk factor for birth outcomes, but TPO antibodies themselves could also have an independent effect .…”
Section: Discussionsupporting
confidence: 73%
“…A population-based cohort from the Netherlands indicated that a high FT4 level in early pregnancy, but not TSH level, are associated with LBW and an increased risk of SGA newborns in euthyroid women [13]. Another Dutch prospective cohort indicated that maternal TSH levels in the upper range of the reference interval in the first and third trimester are independently associated with an increased risk of SGA neonates at term; maternal FT4 levels and TPO-Ab positivity are not associated with SGA offspring [36]. A Spanish cohort study showed a significant inverse correlation of maternal FT4 and TSH levels at the first half of pregnancy with birthweight and indicated that high FT4 levels are associated with an increased risk of SGA [16].…”
Section: Discussionmentioning
confidence: 99%
“…Women with suboptimal thyroid function, mainly those with TPO-antibodies (thyroid-peroxidase-antibody), are at risk for miscarriage and preterm birth [ 9 , 10 ]. Furthermore, there is evidence that high maternal TSH might interfere with normal obstetric outcome at term, with higher incidences of small for gestational age neonates [ 11 ], gestational diabetes [ 10 ] and meconium stained amniotic fluid [ 12 ]. Low FT4 has been associated with poor fetal neurodevelopment and psychomotor development in early childhood [ 13 ].…”
Section: Introductionmentioning
confidence: 99%